2019
DOI: 10.13057/biodiv/d200935
|View full text |Cite
|
Sign up to set email alerts
|

Fingerprinting sengon (Falcatria moluccana) accessions resistant to boktor pest and gall rust disease using microsatellite markers

Abstract: Abstract. Siregar UJ, Rahmawati D, Damayanti A. 2019. Fingerprinting sengon (Falcatria moluccana) accessions resistant to boktor pest and gall rust disease using microsatellite markers. Biodiversitas 20: 2698-2706. Sengon (Falcataria moluccana Miq.) is a multipurpose fast-growing tree species and widely planted as community forest in Indonesia. According to Indonesian Light Wood Association (ILWA) F. moluccana wood products coming from forest industries in Jawa worth US$ 244.46 million export to China alone. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Johnson and (2011) stated that plant growth is controlled by genetics, thus differences in genetic formation will affect the appearance of a particular character. Analysis of genetic diversity using RAPD, SSR, and SNP markers showed grouping between susceptible and resistant sengon plants (Shabrina 2020;Rahmawati 2017;Siregar et al 2019;Yuskianti and Shiraishi 2017). Shabrina et al (2019a) supported this result, which found variances in gene expression in prime sengon plants against sengon plants with gall rust through differential expression gene (DEG) analysis.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Johnson and (2011) stated that plant growth is controlled by genetics, thus differences in genetic formation will affect the appearance of a particular character. Analysis of genetic diversity using RAPD, SSR, and SNP markers showed grouping between susceptible and resistant sengon plants (Shabrina 2020;Rahmawati 2017;Siregar et al 2019;Yuskianti and Shiraishi 2017). Shabrina et al (2019a) supported this result, which found variances in gene expression in prime sengon plants against sengon plants with gall rust through differential expression gene (DEG) analysis.…”
Section: Discussionmentioning
confidence: 81%
“…17 boktor prone trees, 17 gall rust-prone trees, and 16 susceptible trees to both). Susceptible trees referred to those trees that were severely attacked by either boktor pest or gall rust, while resistant trees were the trees as control showing no signs of the pest and disease attacks (Siregar et al 2019). The seeds as control were extracted from adjacent trees and grow on the same plot to minimize environmental influences.…”
Section: Seed Extraction and Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has shown that among mostly susceptible trees, some trees are resistant and have higher levels of enzyme inhibitory activity [ 5 ]. Efforts to differentiate between these two accessions using microsatellite markers have failed to provide satisfactory answers [ 6 ] as the mechanisms involved in tropical tree resistance to phytophagous pests remain largely unknown. Technological advances have allowed us to perform large-scale and rapid sequencing using next-generation sequencing (NGS) platforms to obtain genomic and transcriptomic data for perennial plants, especially trees, to accelerate tree improvement programs [ 7 9 ].…”
Section: Objectivementioning
confidence: 99%
“…With the except for genetic characterization of highly infested and healthy Falcata trees (Siregar et al 2019) and the presence of Boktor digestive enzymes inhibitors (Siregar et al 2020), information about internal host factors that influencing Boktor infestation is still limited. Therefore, this research aimed to analyze the characteristics of chemical components on Falcata woods aged 2, 3, and 4 years to determine which chemical components contribute to Boktor infestation.…”
Section: Introductionmentioning
confidence: 99%